Cyclic reactivation of distinct feature dimensions in human visual working memory - Rebecca Rosa Schmid; Ulrich Pomper; Ulrich Ansorge (Acta Psychologica, 2022)
Several recent behavioral studies have observed 4–10 Hz rhythmic fluctuations in attention-related performance over time. So far, this rhythmic attentional sampling has predominantly been demonstrated with regards to external visual attention, directed toward one single feature dimension. Whether and how attention might sample from concurrent internal representations of different feature dimensions held in working memory (WM) is currently largely unknown.To elucidate this issue, we conducted a human behavioral dense-sampling experiment, in which participants had to hold representations of two distinct feature dimensions (color and orientation) in WM. By querying the contents of WM at 72 time-points after encoding, we estimated the activity time course of the individual feature representations. Our results demonstrate an oscillatory component at 9.4 Hz in the joint time courses of both representations, presumably reflecting a common early perceptual sampling process in the alpha-frequency range. Furthermore, we observed an oscillatory component at 3.5 Hz in the time course difference between the two representations. This likely corresponds to a later attentional sampling process and indicates that internal representations of distinct features are activated in alteration.In summary, we demonstrate the cyclic reactivation of internal WM representations of distinct feature dimensions, as well as the co-occurrence of behavioral fluctuations at distinct frequencies, presumably associated to internal perceptual- and attentional rhythms. In addition, our findings also challenge a model of strict parallel processing in visual search, thus, providing novel input to the ongoing debate on whether search for more than one target feature constitutes a parallel- or a sequential mechanism.